PARTISIPASI MASYARAKAT DALAM ANALISIS MENGENAI DAMPAK LINGKUNGAN HIDUP (Studi Kasus pada Masyarakat Kecamatan Gunem Atas Pembangunan Pabrik PT. Semen Indonesia di Kabupaten Rembang) - Aditya Aria Pradana Putra; Nunik Retno (Journal of Politic and Government Studies, 2019)
In a country that has a democratic system, one indication of the running of democracy is the active role of the community in various fields and decision making. Referring to the basics in the process of preparing the Environmental Impact Analysis (EIA) mandated by Law Number 32 of 2009 and regulated in the Regulation of the Minister of Environment No. 17 of 2012 The research method used in this essay writing is a qualitative research method. The data source in this study uses primary data and secondary data. Data collection techniques used are document studies, and direct interviews. The results of the study showed that community involvement in the process of preparing the EIA in Rembang District was in accordance with the Regulation of the Minister of Environment No. 17 of 2012. However, there are still obstacles in the process of involvement, both technical and technical. own general constraints. Suggestions from the results of this study are to further socialize the process of community involvement itself, as well as provide assistance to the community itself. and make online services for complaints and consultations. In addition to the regional government, they must coordinate with relevant agencies and maintain neutrality on the red plate, yellow plate and black plate so that later the decision does not harm the parties concerned.Keywords : Keterlibatan Masyarakat, AMDAL, PT. Semen Indonesia, Kabupaten Rembang.